LEGAL REGULATION OF SERVICE INVENTIONS: PROTECTING THE INTERESTS OF THE INVENTOR AND THE EMPLOYER (European Journal of Economics, Finance and Business Development, 2025)
The article compares the legal regimes governing service inventions in Uzbekistan, the United Kingdom, and the Netherlands. It examines the criteria by which patent rights pass from employee to employer and the rules for author’s compensation. The analysis reveals gaps in the Uzbek model (contractual uncertainty, absence of sanctions for patent lapse) and shows how the British “fair share” mechanism and the Dutch requirement of “proportionate remuneration” address similar issues. Recommendations are offered: introduce a methodology for calculating payments, oblige the employer to disclose the commercial effect of the invention, and create a pre-trial mediation body.